High-Dose Amoxicillin with Clavulanate for the Treatment of Acute Otitis Media in Children - Chia-Huei Chu; Mao-Che Wang; Liang-Yu Lin; Tzong-Yang Tu; Chii-Yuan Huang; Wen-Huei Liao; Ching-Yin Ho; An-Suey Shiao (The Scientific World Journal)
Objective. This study uses the acute otitis media clinical practice guideline proposed in 2004 as a reference to evaluate whether antibiotics doses that are in line with the recommendations lead to better prognosis. The study also attempts to clarify possible factors that influence the outcome. Study Design. Retrospective cohort study. Subjects and Methods. A total of 400 children with acute otitis media were enrolled. The dosage of amoxicillin was considered to be appropriate when in accord with clinical practice guidelines, that is, 80–90 mg/kg/day. The outcome was defined according to the description of tympanic membrane on medical records. Multivariate logistic regression was used to analyze the relationship between antibiotic dosage and prognosis after adjusting for baseline factors. Results. The majority of prescriptions were under dosage (89.1%) but it was not noticeably associated with outcome (P= 0.41). The correlation between under dosage and poor prognosis was significant in children below 20 kg with bilateral acute otitis media (odds ratio 1.63; 95% CI 1.02–2.59, P=0.04). Conclusion. Treating acute otitis media in children, high-dose amoxicillin with clavulanate as recommended in the clinical practice guideline was superior to conventional doses only in children under 20 kg with bilateral diseases.